Effect of Physical Activity on the Progression of Alzheimer's Disease: The Clinical Research Center for Dementia of South Korea Study. - Minn, Yang-Ki; Choi, Seong Hye; Suh, Young Ju; Jeong, Jee Hyang; Kim, Eun-Joo; Kim, Jong Hun; Park, Kyung Won; Park, Moon Ho; Youn, Young Chul; Yoon, Bora; Choi, Seok-Jin; Oh, Youn Kyung; et al. (J Alzheimers Dis, 2018)
BACKGROUND: There is a lack of research on the effects of physical activity (PA) on the progression of Alzheimer's disease (AD). OBJECTIVES: We investigated whether PA is associated with progression of dementia and mortality in AD. METHODS: In the present study, 934 patients with mild-to-moderate AD were included. PA was evaluated using a questionnaire written by the caregiver. The outcome measures were the Clinical Dementia Rating-Sum of Boxes (CDR-SB), Seoul-Instrumental Activities of Daily Living (S-IADL), Caregiver-Administered Neuropsychiatric Inventory (CGA-NPI), a global composite score of neuropsychological subtests, and mortality. They were evaluated annually and received a maximum of three follow-up examinations. RESULTS: Between-group differences compared with the no PA group in the change of CDR-SB scores were -0.431 (95% CI = -0.824∼-0.039; p = 0.031) for the moderate PA group (150-750 minutes per week of moderate intensity PA), and -1.148 (-1.656∼-0.639; p < 0.001) for the high PA group (>750 minutes per week). As PA increased, there was a significant trend to slow the rate of increase in the CDR-SB, S-IADL, and CGA-NPI scores. The patients with ≥150 minutes per week for each of non-recreational and recreational PAs had a lower risk of mortality compared to those with <150 minutes per week for each of the PAs (hazard ratio 0.22, 95% CI = 0.05∼0.88; p = 0.033). CONCLUSION: More PA is associated with slower progression of dementia severity, functional decline, and abnormal behavior, and with a lower risk of mortality in AD.

Effectiveness of Anti-Dementia Drugs in Extremely Severe Alzheimer's Disease: A 12-Week, Multicenter, Randomized, Single-Blind Study. - Hong, Yun Jeong; Choi, Seong Hye; Jeong, Jee Hyang; Park, Kyung Won; Na, Hae Ri (J Alzheimers Dis, 2018)
BACKGROUND/OBJECTIVE: There is insufficient evidence to guide decisions concerning how long anti-dementia drug (ADD) regimens should be maintained in severe Alzheimer's disease (AD). We investigated whether patients with extremely severe AD who were already receiving donepezil or memantine benefited from continuing treatment. METHODS: In this randomized and rater-blinded trial, 65 AD patients with a Mini-Mental State Examination score from 0 to 5 and a score of 6c or worse on Functional Assessment Staging were randomly assigned to an ADD-continuation group (N = 30) or an ADD-discontinuation group (N = 35). The current use of donepezil or memantine was maintained for 12 weeks in the ADD-continuation group and was discontinued after baseline in the ADD-discontinuation group. Efficacy measures were obtained at baseline and 12 weeks. The primary efficacy variable was the change from baseline to the end of the study in Baylor Profound Mental State Examination (BPMSE) scores. RESULTS: The change in the BPMSE from baseline to the end of the study in the ADD-continuation group (a 0.4-point improvement) was not equivalent to that in the ADD-discontinuation group (a 0.5-point decline), as determined by two one-sided tests of equivalence. Study withdrawals due to adverse events (11.4% versus 6.7%) were more frequent in the ADD-discontinuation group than in the ADD-continuation group. CONCLUSION: Continued treatment with donepezil or memantine seems unequal and might be superior to withdrawal of the drugs in terms of the effects on global cognition in patients with extremely severe AD. Current Controlled Trials number: KCT0000874 (CRIS).

Mortality Risk after Diagnosis of Early-Onset Alzheimer's Disease versus Late-Onset Alzheimer's Disease: A Propensity Score Matching Analysis. - Chang, Ki Jung; Hong, Chang Hyung; Lee, Kang Soo; Kang, Dae Ryong; Lee, Jeong Dong; Choi, Seong Hye; Kim, Seong Yoon; Na, Duk L; Seo, Sang Won; Kim, Do-Kwan; Lee, Yunhwan; Chung, Young Ki; et al. (J Alzheimers Dis, 2017)
BACKGROUND/OBJECTIVE: We aimed to compare the risk of mortality in patients with early-onset Alzheimer's disease (EOAD) versus those with late-onset AD (LOAD) using a large number of study subjects. We applied propensity score matching (PSM) to minimize confounding biases in the comparison between EOAD and LOAD. METHODS: We obtained data from elderly Korean subjects with AD (n = 3,611) at baseline from the CREDOS cohort study, which was conducted from November 2005 to July 2013. We conducted PSM to reduce the bias due to confounding variables related to survival in patients with AD. The risks of mortality associated with EOAD and LOAD were evaluated by Cox proportional hazard analyses, controlling for relevant covariates. RESULTS: After propensity score matching, 312 subjects with EOAD and 624 subjects with LOAD were selected for further analysis. The Cox proportional hazard analysis showed that patients with EOAD are at a greater risk for mortality compared to those with LOAD (Hazard Ratio: 2.01, 95% CI: 1.01-4.00, p-value: 0.04) when controlling for the direct effect of aging on mortality. The results did not change after adjusting for age at diagnosis, general cognitive function, nutritional factor related to body mass index, and physical disability using activities of daily living. The results support the assumption that EOAD takes a more malignant course than LOAD. CONCLUSIONS: Our results provide support for the idea that EOAD takes a clinical course that is distinct from that of LOAD, especially as pertains to the risk of mortality.

Occupational Attainment as Risk Factor for Progression from Mild Cognitive Impairment to Alzheimer's Disease: A CREDOS Study. - Myung, Woojae; Lee, Chunsoo; Park, Jin Hong; Woo, Sook-Young; Kim, Seonwoo; Kim, Sangha; Chung, Jae Won; Kang, Hyo Shin; Lim, Shinn-Won; Choi, Junbae; Na, Duk L; Kim, Seong Yoon; et al. (J Alzheimers Dis, 2017)
High occupational attainment has been known as a marker of cognitive reserve. Previous studies in the general population have shown that high occupational attainment is associated with reduced risk of Alzheimer's disease (AD). However, few studies have assessed the effect of occupational attainment on the clinical course of mild cognitive impairment (MCI). In this study, we evaluated whether individuals with high occupational attainment show more frequent progression from MCI to AD. Participants (n = 961) with MCI were recruited from a nationwide, hospital-based multi-center cohort, and were followed for up to 60 months (median: 17.64, interquartile range [12.36, 29.28]). We used Cox regression for competing risks to analyze the effect of occupational attainment on development of AD, treating dementia other than AD as a competing risk. Among the 961 individuals with MCI, a total of 280 (29.1%) converted to dementia during the follow-up period. The risk of progression to AD was higher in the individuals with high occupational attainment after controlling for potential confounders (hazard ratio = 1.83, 95% confidence interval = 1.25-2.69, p = 0.002). High occupational attainment in individuals with MCI is an independent risk factor for higher progression rate of MCI to AD. This result suggests that the protective effect of high occupational attainment against cognitive decline disappears in the MCI stage, and that careful assessment of occupational history can yield important clinical information for prognosis in individuals with MCI.

Prediction Model of Conversion to Dementia Risk in Subjects with Amnestic Mild Cognitive Impairment: A Longitudinal, Multi-Center Clinic-Based Study. - Jang, Hyemin; Ye, Byoung Seok; Woo, Sookyoung; Kim, Sun Woo; Chin, Juhee; Choi, Seong Hye; Jeong, Jee Hyang; Yoon, Soo Jin; Yoon, Bora; Park, Kyung Won; Hong, Yun Jeong; Kim, Hee Jin; et al. (J Alzheimers Dis, 2017)
BACKGROUND: Patients with amnestic mild cognitive impairment (aMCI) have an increased risk of dementia. However, conversion rate varies. Therefore, predicting the dementia conversion in these patients is important. OBJECTIVE: We aimed to develop a nomogram to predict dementia conversion in aMCI subjects using neuropsychological profiles. METHODS: A total of 338 aMCI patients from two hospital-based cohorts were used in analysis. All patients were classified into 1) verbal, visual, or both, 2) early or late, and 3) single or multiple-domain aMCI according to the modality, severity of memory dysfunction, and multiplicity of involved cognitive domains, respectively. Patients were followed up, and conversion to dementia within 3 years was defined as the primary outcome. Our patients were divided into a training data set and a validation data set. The associations of potential covariates with outcome were tested, and nomogram was constructed by logistic regression model. We also developed another model with APOE data, which included 242 patients. RESULTS: In logistic regression models, both modalities compared with visual only (OR 4.44, 95% CI 1.83-10.75, p = 0.001), late compared to early (OR 2.59, 95% CI 1.17-5.72, p = 0.019), and multiple compared to single domain (OR 3.51, 95% CI 1.62-7.60, p = 0.002) aMCI were significantly associated with dementia conversion within 3 years. A nomogram incorporating these clinical variables was constructed on the training data set and validated on the validation data set. Both nomograms with and without APOE data showed good prediction performance (c-statistics ≥ 0.75). CONCLUSIONS: This study showed that several neuropsychological profiles of aMCI are significantly associated with imminent dementia conversion, and a nomogram incorporating these clinical subtypes is simple and useful to help to predict disease progression.

Clinical Conversion or Reversion of Mild Cognitive Impairment in Community versus Hospital Based Studies: GDEMCIS (Gwangju Dementia and Mild Cognitive Impairment Study) and CREDOS (Clinical Research Center for Dementia of South Korea). - Roh, Hyun Woong; Hong, Chang Hyung; Lee, Yunhwan; Lee, Kang Soo; Chang, Ki Jung; Kang, Dae Ryong; Lee, Jung-Dong; Choi, Seong Hye; Kim, Seong Yoon; Na, Duk L; Seo, Sang Won; Kim, Doh Kwan; et al. (J Alzheimers Dis, 2016)
BACKGROUND: In keeping with increasing interest in dementia, few recent studies suggest that clinical course of mild cognitive impairment vary across different studies with hospital-based subjects showing higher rates of conversion than community-based subjects. OBJECTIVE: The main objective of the present study was to assess whether the clinical conversion or reversion rates differ according to recruitment source. METHODS: The baseline study subjects comprised of patients who were diagnosed with mild cognitive impairment in community-based GDEMCIS or hospital-based CREDOS. The two studies had nearly the same protocol and were performed over a similar period. We used propensity score matching for baseline comparability. After that, Cox proportional hazards regression analyses were conducted to estimate the hazard ratios and 95% confidence intervals of clinical conversion or reversion. RESULTS: Based on 89 GDEMCIS subjects, 1 : 4 propensity score matching was conducted and 356 CREDOS subjects were selected. After adjusting for covariates including baseline demographics, comorbidity, depression, disability, and neuropsychological result, Cox proportional hazard regression analysis for time to clinical conversion indicated that recruitment from hospital-based CREDOS exhibited hazard ratio of 2.13 (95% CI, 1.08-4.21), as compared to recruitment from community-based GDEMCIS. Similarly, Cox proportional hazard regression analysis for time to reversion indicated that recruitment from hospital-based CREDOS exhibited hazard ratio of 0.34 (95% CI, 0.20-0.59), as compared to recruitment from community-based GDEMCIS. CONCLUSION: The present study demonstrated that even after the matching process and adjustments for baseline covariates, recruitment source greatly affected the course of mild cognitive impairment.

Differences in Depressive Patterns According to Disease Severityin Early-Onset Alzheimer's Disease. - Yoon, Bora; Yang, Dong Won; Hong, Yun Jeong; Choi, Seong Hye; Park, Sun Ah; Park, Hee Kyung; Kim, Yong Duk; Shim, Yong S (J Alzheimers Dis, 2016)
BACKGROUND & OBJECTIVE: Depression frequently combines with dementia, including early-onset Alzheimer's disease (EOAD). We investigated differences in prevalence and characteristics of depressive symptoms according to dementia severity in EOAD patients. METHODS: The 15-item Korean version of the Geriatric Depression Scale (GDS-15) was administered to 412 EOAD patients. Factor analysis was used to assess GDS-15 factor structure. We subdivided participants into three groups by disease severity, then compared the frequencies and scores of individual GDS-15 items and performed logistic regression analysis to assess associations between depressive symptoms and EOAD stage. RESULTS: Factor analysis yielded three factor categories: 1) "hopelessness and ominousness" (symptoms no. 6, 8, 12, 14, 15); 2) "unhappiness and dissatisfaction" (no. 1, 3, 5, 7, 11); and 3) "monotony and lack of energy" (no. 2, 4, 9, 10, 13). Factor 2 depressive symptoms (no. 1, 5, 11) were less common in moderate EOAD. The risk of Factor 1 symptoms: no. 12 (OR, 2.04; 95% CI, 1.19-3.50; p = 0.010) and 14 (OR, 1.84; 95% CI, 1.07-3.16; p = 0.028) was higher in mild than very mild EOAD. The risk of Factor 2 symptoms: no. 9 (OR, 2.69; 95% CI, 1.08-6.71; p = 0.033) and 13 (OR, 2.12; 95% CI, 1.02-4.40; p = 0.043) was higher in moderate than mild EOAD. CONCLUSION: We confirmed that depressive symptoms differ according to EOAD severity. When assessing depressive symptoms related to dementia progression, we recommend focusing on "hopelessness and ominousness" in very mild EOAD and "unhappiness and dissatisfaction" in mild EOAD.

Predictive factors for disease progression in patients with early-onset Alzheimer's disease. - Yoon, Bora; Shim, Yong S; Park, Hee-Kyung; Park, Sun Ah; Choi, Seong Hye; Yang, Dong Won (J Alzheimers Dis, 2016)
BACKGROUND: Only a few studies have investigated disease progression in patients with early-onset Alzheimer's disease (EOAD). Therefore, the aim of this study was to investigate disease progression in patients with EOAD and the influence of various factors, such as gender, education, and apolipoprotein E (APOE) genotype on disease progression. METHODS: A total of 288 EOAD patients were enrolled in the study. Linear mixed models were used to investigate the rate of cognitive and functional decline in terms of age at onset, gender, education, follow-up period, and APOE genotype. RESULTS: EOAD patients showed an annual decline of -1.54 points/years in the Korean version mini-mental examination score, an annual increase of 3.46 points/year in the Seoul instrumental activities of daily living (SIADL) score, and an annual increase of 1.15 points/year in the clinical dementia rating scale-sum of boxes score. After stratification, higher educated patients showed faster disease progression in all three parameters, and female patients demonstrated faster disease progression as assessed by the SIADL score. Age at onset and APOE genotype had no influence on disease progression. CONCLUSION: We confirmed the rate of disease progression in Korean patients with EOAD in real-life hospital-based clinical practice. The results of this study suggest that education and female gender, not APOE genotype, may be important as independent strong predictive factors for disease progression in patients with EOAD.
Keywords: Activities of Daily Living; Adult; Age Factors; Aged; Alleles; Alzheimer Disease; Apolipoproteins E; Disease Progression; Female; Genotype; Humans; Linear Models; Longitudinal Studies; Male; Middle Aged; Neuropsychological Tests; Risk Factors; Sex Factors

Unstable Body Mass Index and Progression to Probable Alzheimer's Disease Dementia in Patients with Amnestic Mild Cognitive Impairment. - Ye, Byoung Seok; Jang, Eun Young; Kim, Seong Yoon; Kim, Eun-Joo; Park, Sun Ah; Lee, Yunhwan; Hong, Chang Hyung; Choi, Seong Hye; Yoon, Bora; Yoon, Soo Jin; Na, Hae Ri; Lee, Jae-Hong; et al. (J Alzheimers Dis, 2016)
BACKGROUND AND OBJECTIVE: We investigated the influence of body mass index (BMI) status at baseline and changes in BMI over a follow-up period on the development of dementia in amnestic mild cognitive impairment (aMCI) patients. METHODS: The longitudinal data of 747 aMCI patients were used to investigate the relationships among baseline BMI status, subsequent changes in BMI (median follow-up duration: 1.6 years, interquartile range: 1.0-2.3 years), and risk of progression to probable Alzheimer's disease dementia (pADD). The aMCI patients were classified into underweight, normal weight, overweight, and obese subgroups, and further categorized into increased BMI, stable BMI, and decreased BMI subgroups during follow-up using a 4% mean annual change in BMI cut-off value. RESULTS: Compared to the normal weight group, the underweight group had a higher risk of pADD (hazard ratio [HR]: 1.89, 95% confidence interval [CI]: 1.07-3.37) while the obese group had a lower risk (HR: 0.70, 95% CI: 0.49-0.999). After controllingfor baseline BMI status, the decreased BMI (HR: 2.29, 95% CI: 1.41-3.72) and increased BMI (HR: 3.96, 95% CI: 2.62-6.00) groups were at increased risk of progression to pADD. CONCLUSIONS: Our findings suggested that underweight at baseline was associated with a higher risk of progression to pADD, while obesity at baseline predicted a lower risk. Furthermore, significant changes in BMI during the follow-up period reflected an increased risk of progression to pADD, regardless of BMI status at baseline.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Analysis of Variance; Body Mass Index; Body Weight; Cognitive Dysfunction; Dementia; Disease Progression; Female; Humans; Kaplan-Meier Estimate; Longitudinal Studies; Male; Neuropsychological Tests; Registries

Body Mass Index and Mortality Rate in Korean Patients with Alzheimer's Disease. - Jang, Hyemin; Kim, Jong Hun; Choi, Seong Hye; Lee, Yunhwan; Hong, Chang Hyung; Jeong, Jee Hyang; Han, Hyun Jeong; Moon, So Young; Park, Kyung Won; Han, Seol-Hee; Park, Kee Hyung; Kim, Hee Jin; et al. (J Alzheimers Dis, 2015)
Background: A relationship between body weight, cognitive impairment, and the onset of Alzheimer's disease (AD) was recently reported. However, to our knowledge, no studies have investigated the relationship between body weight and mortality in Asian AD patients. Objective: We evaluated the relationship between body mass index (BMI) and mortality rate in Korean AD cohorts. Methods: Participants were consecutively included from two Korean representative registries: 579 AD patients from Samsung Medical Center and 1911 AD patients from the Clinical Research Center for Dementia of South Korea study. We combined these two AD cohorts to evaluate the association between BMI and mortality. BMI was used to categorize the participants into underweight, normal-weight, overweight, and obesity subgroups. All deaths were confirmed through the nationwide mortality database of Statistics Korea. Results: 53 of 181 (29.3%), 208 of 1,127 (18.5%), 88 of 626 (14.1%), and 115 of 556 (20.7%) patients died in the underweight, normal-weight, overweight, and obese subgroups during 43.7 months of follow-up. The time-dependent cox proportional hazards model showed that, relative to the normal-weight subgroup, the underweight group had higher mortality (HR 1.82 (95% CI, 1.07-3.09)) while overweight group had lower mortality rate (HR 0.60 (95% CI, 0.38-0.95)) The effects of underweight and overweight were prominent in younger and older elderly group, respectively. However, there were no interactive effects of dementia severity or gender and BMI on survival rate. Conclusion: Relative to AD patients of normal weight, those who were underweight had an increased mortality rate, and overweight predicted decreased mortality in AD patients. Furthermore, our findings may help facilitate mortality stratification in AD patients by using baseline BMI.